Suicidal behavior among teenagers: A review - Muhammad Ishaq; Shah, Muslim; Taufiq Meghani, Shaista; Punjani, Neelam (International Journal of Endorsing Health Science Research, 2014)
After every 16 minutes one individual die not merely from a disease or an accident but intentionally through suicide. Literature reveals that it is a long process usually stretches over years from suicidal ideation to planning and finally an attempt. The causes of suicidal behavior are immense which captivate these poor and innocent creatures in great troubles. In teenagers the suicidal ideations are related to multiple internal and external factors. They consume different lethal liquids and adopt different methods for performing this violent act. Further on its impact is not only on her individual and family life but has a great impact on the society as well. It is not an essay task to eradicate this violent act but as we a responsible member of the society we can assess their suffering and agony and help them identifying different social groups. Along with it we can also prevent the suicide at three different levels that’s primary secondary and tertiary. We can also do the counseling. In conclusion, I would say that it is a rising issue of today’s world and we all must give our efforts to show a reduction in its prevalence.